2020
DOI: 10.3389/fspor.2020.518148
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on the Longitudinal Effects of Unilateral Knee Extension Exercise on Muscle Strength

Abstract: The aim of the study was to investigate the time-dependent increase in the knee extensors' isometric strength as a response to voluntary, unilateral, isometric knee extension exercise (UIKEE). To do so, a systematic review was carried out to obtain data for a Bayesian longitudinal model-based meta-analysis (BLMBMA). For the systematic review, PubMed, Web of Science, SCOPUS, Chochrane Library were used as databases. The systematic review included only studies that reported on healthy, young individuals performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
(237 reference statements)
0
3
0
Order By: Relevance
“…Isometrics have enjoyed a resurgence in popularity in recent times, this being attributed to many reasons: 1) isometric assessments are typically easy to administer, safe and a more time-efficient method to measure maximal strength than traditional 1RM testing [2]; 2) it's a reliable way to test maximal strength and peak force in youth and adult athletes [3]; 3) some of the performance variables from isometric assessments have been shown to significantly correlate to athletic movements such as the vertical jump and sprint speed [4]; 4) isometrics can be performed at multiple angles and can be used to train 'weak points/sticking regions' [5]; 5) isometrics can provide variability to your programming; 6) in some activities or sports, isometric strength is key to performance e.g. isometric core strength of sprinters to combat angular momentum of the limbs; 7) isometric contractions results in less fatigue compared with high intensity concentric contractions; 8) produces less stress on the body, due to lower impact forces, reducing injury risk [6]; (9) isometrics as a training method can be used in training programs to develop strength, power, muscle size and tendon stiffness; 10) one of the greatest benefits is its accessibility, being that it can take place anywhere at any time, whether sitting in a plane or working out in a gym and, 11) effectively improves one's strength after injury whilst minimizing pain and risk of reinjury [7].…”
Section: Introductionmentioning
confidence: 99%
“…Isometrics have enjoyed a resurgence in popularity in recent times, this being attributed to many reasons: 1) isometric assessments are typically easy to administer, safe and a more time-efficient method to measure maximal strength than traditional 1RM testing [2]; 2) it's a reliable way to test maximal strength and peak force in youth and adult athletes [3]; 3) some of the performance variables from isometric assessments have been shown to significantly correlate to athletic movements such as the vertical jump and sprint speed [4]; 4) isometrics can be performed at multiple angles and can be used to train 'weak points/sticking regions' [5]; 5) isometrics can provide variability to your programming; 6) in some activities or sports, isometric strength is key to performance e.g. isometric core strength of sprinters to combat angular momentum of the limbs; 7) isometric contractions results in less fatigue compared with high intensity concentric contractions; 8) produces less stress on the body, due to lower impact forces, reducing injury risk [6]; (9) isometrics as a training method can be used in training programs to develop strength, power, muscle size and tendon stiffness; 10) one of the greatest benefits is its accessibility, being that it can take place anywhere at any time, whether sitting in a plane or working out in a gym and, 11) effectively improves one's strength after injury whilst minimizing pain and risk of reinjury [7].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to localized PAPE, little is known about the possibility to obtain a nonlocalized PAPE on muscles that were not involved in the resistance exercise protocol. Despite several studies demonstrating that a cross-education may be produced by unilateral resistance training (3), Andrews et al (4) reported that a single-leg squat protocol, performed with the dominant leg, did not elicit any improvement in the power performance of the contralateral leg. To the best of our knowledge, only Cuenca-Fernández et al (17) have investigated the existence of a nonlocalized PAPE between the upper and lower body.…”
Section: Introductionmentioning
confidence: 99%
“…(1) no specific potentiating warmup (control); (2) a traditional plyometric warmup (3) a short duration (15s) isometric lunge hold; and (4) a long duration isometric lunge hold (30s). The selection of the isometric split squat and the protocols were chosen for its practical application and support from the research observing the effects on unilateral isometric knee extension exercise (UIKEE) (Altan et al, 2020& Place et al, 2005. It has been observed that the use of UIKEE has positive effects on strength within four weeks of training as well as supporting tendon quality of the lower limbs.…”
Section: Future Researchmentioning
confidence: 99%